Analiza i wizualizacja zmian w strukturze wydatków konsumpcyjnych w Polsce na tle krajów Unii Europejskiej - Grześkowiak, Alicja (Analysis and Visualization of Changes in the Structure of Consumer Expenditure in Poland in Comparison to other European Union Countries, 2009)
The paper presents changes in the structure of consumer expenditure. The author performed a comprehensive analysis of chosen categories of goods and services connected with meeting both basic and higher order needs. A specific method of visualization was applied to reflect the changes occurring in Poland with reference to other European Union countries. Similarities of the level and the performance of the analyzed goods and services shares were evaluated and a graphical presentation allowing the interpretation of the degree of the similarity was suggested.
2023 Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 232-241